Impact of FLD Intervention on Awareness and Skill to Adopt Good Agricultural Practices of Isabgol Crop in Kachchh District of Gujarat - Ramniwas; Kanwat, Manish; Jat, Sita Ram (Annals of Arid Zone, 2023)
Frontline demonstration (FLD), aims to boost productivity by offering necessaryinputs as well as enhanced production and good agricultural techniques that have beentested by the researchers. Krishi Vigyan Kendra (ICAR-CAZRI), Kukma, Bhuj organisedfront-line demonstrations (FLDs) on isabgol in various villages in the Anjar, Bhuj andNakhatrana Talukas of Kachchh from 2018-19 to 2020-21. The front line demonstrationprogram were successfully examined the shatter-resistant high-yielding variety GujaratIsabgol-4 in a farmer’s fields (FLDs). Fifty pro-tests against farming practises werestaged in a 20 ha area at a farmers’ field in the arid region of Kachchh. The averagegrain yield under the enhanced practise grew significantly by 11.75% of the averageof the farmers’ practise output, from 950 kg ha -1 to 1061.67 kg ha -1 . The extension gap,technology gap and technology index were averaged as 111.67 kg ha -1 , 238.33 kg ha -1 and18.33%, respectively. Farmers received higher average returns of Rs 11943.33 ha -1 and aB:C ratio of 3.04 as a result of improved practises. The KVK (Kachchh-II) successfullycarried out extension activities during that time period to assist the targeted farmersright away, comprising farmer training, literature distribution, diagnostic visits, etc.The Frontline demonstrations program created greater awareness, attitude and skill toadopt good agricultural practises in isabgol, which therefore, increased their productionand economics.